Learning from COVID-19: how Indonesian English teachers see computer-assisted language learning? - Rizkiana Maharddhika; Mushoffan Prasetianto (Institute of Advanced Engineering and Science, 2024)
The COVID-19 outbreak has transformed various parts of life, including teaching and learning methods. Teachers, especially Indonesian English teachers, were taken aback by the abrupt transition from offline to online instruction because it was unanticipated and unprepared. This paper attempted to investigate how teachers implement their pedagogical knowledge in the online environment during the pandemic and how they improve on using computer-assisted language learning (CALL) during the sudden shift from offline to online instruction. The findings revealed that teaching methods are being adapted to accommodate the features of the online platform. In order to adjust to this new situation, teachers use their creativity to adapt the stages of cooperative learning, collaborative learning, and class discussion in an online context. Participating in virtual workshops and training also helps teachers improve their digital skills concerning internet material. In the future, the results of the present study can be applied to improve the teacher education curriculum. Specifically, it is suggested to construct a course for the teacher education curriculum that places pre-service teachers in diverse and challenging conditions.